Metode Komunikasi dengan Keluarga sebagai Peserta Didik di Badan Intelijen Negara - Alisyah Salsabila; Naila Khairunisa; Annisa Agustin Wibowo; Annisa Sharfina; Yani Achdiani; Sarah Nurul Fatimah (Badan Penerbit STIEPARI Press, 2025)
The life of students in the National Intelligence Agency (BIN) is unique because it is bound by rules and education systems that are closed, structured, and have a high level of confidentiality. This situation often creates communication distance between students and their families, especially in terms of information disclosure and limited interaction time. This research aims to examine communication methods that can be applied by learners in establishing healthy and effective relationships with their families. The approach used is a literature study of various journals, books, and scientific articles relevant to interpersonal communication, family communication, and communication in military or intelligence institutions. The results of the analysis show that the use of assertive, empathic, and adaptive communication is the main key in maintaining harmonious relationships. In addition, the importance of emotional support from the family is also a supporting factor for students' academic and psychological success. Communication that is reciprocal, open within certain limits, and carried out consistently can strengthen emotional bonds even in situations full of limitations. This article recommends the importance of interpersonal communication training for learners, as well as briefing families on the characteristics of education in the BIN environment.